Studying Preferences and Concerns about Information Disclosure in Email Notifications - Kim, Yongsung; Fourney, Adam; Kamar, Ece (The Web Conference (WWW '19), 2019)
People receive dozens, or hundreds, of notifications per day and each notification poses some risk of accidental information disclosure in the presence of others; onlookers may see notifications on a mobile phone lock screen, on the periphery of a desktop or laptop display. We quantify the prevalence of these accidental disclosures in the context of email notifications, and we study people’s relevant preferences and concerns. Our results are compiled from a retrospective survey of 131 respondents, and a contextual-labeling study where 169 participants labeled 1,040 meeting-email pairs. We find that, for 53% of people, at least 1 in 10 email notifications poses an information disclosure risk, and the real or perceived severity of these risks depend both on user characteristics and the meeting or email attributes. We conclude by exploring machine learning for predicting people’s comfort levels, and we present implications for the design of future social-context aware notification systems.